Insights of structural and functional luteolytic pattern inTharparkar cows (Bos indicus) through doppler ultrasonography - GAWAI, MOHAN; KUMAR, BRIJESH; MEHROTRA, SANJEEV; SAHU, UTTAM KUMAR; WARGHAT, CHINMAY; DONADKAR, MANOJ; CHANDRA, PRADEEP; LOKAVYA, ATHIDI; VANDANA; PATRA, MK; SINGH, SK; KHAN, MH (The Indian Journal of Animal Sciences, 2026)
The study aimed to investigate real-time changes in intraluteal blood flow, progesterone (P4) profile, and associated structural alterations in the corpus luteum (CL) of Tharparkar cows following prostaglandin F2α (PGF2α) administration. Tharparkar cows (n = 8), at least 60 days postpartum with a well-developed CL, were administered cloprostenol (500 μg, intramuscularly). Ultrasonographic examinations and blood sampling were performed at 0, 0.5, 1, 2, 4, 8, 12, 24, 48, and 72 h post-injection. CL diameter remained unchanged up to 4 h post-treatment, followed by a significant reduction (p < 0.05) beginning at 12 h and progressing through 24, 48, and 72 h, indicating structural luteolysis. The mean CL diameter decreased from 20.29 ± 1.19 mm at 0 h to 11.55 ± 0.30 mm at 72 h. Anacute increase in intraluteal blood flow was observed, peaking at 1 h post-injection, followed by a significant decline (p < 0.05), with the lowest values recorded at 72 h. Serum P4 concentrations decreased significantly (p < 0.05) from 1 h onward, confirming functional luteolysis. The findings demonstrated a biphasic vascular response characterized by an initial rise followed by a sustained decline in blood flow, coupled with progressive structural regression of the CL. The study provided important insights into the hemodynamic and functional dynamics of PGF2α-induced luteolysis in Bos indicus cows.